Self-healing epoxy coating with microencapsulation of linseed oil for the corrosion protection of Magnesium (Mg) - Juliawati, Alias; N. A., Johari; A., Zanurin; Nasrul Azuan, Alang; M. Z. M., Zain (IOP Publishing, 2021)
The ability to self-heal is an important feature for the long-term durability of protective coatings on metal alloys. Microcapsules in the self-healing coating allowed for automatic recovery of any damages or cracks, extending the life of the coating. In this study, self-healing microcapsules containing linseed oil as the core material and polyurea-formaldehyde (PUF) as the shell material were manufactured to epoxy resin matrix. Coatings were applied to a bare magnesium (Mg) substrate and scratched to test the self-healing ability. Optical and scanning electron microscopy (SEM) were used to characterize the microcapsules formed by varied stirring rates of 300 and 800 rpm. By using potentiodynamic polarization in a 3.5 wt.% NaCl solution, the corrosion rate of embedded microcapsules and coatings on Mg was evaluated, and the corrosion rate was studied using the Tafel plot. As a consequence, the epoxy coating containing linseed oil and urea formaldehyde, stirred at 800 rpm, significantly resists corrosion attack on the magnesium sheet, with decreased corrosion current density, icorr (1.552 μA/cm2) as compared to the bare magnesium sheet (109.8 μA/cm2). During the microcapsule preparation, increasing the stirring rate from 300 to 800 rpm reduces the icorr value by roughly half. As a result, the self-healing coatings demonstrated adequate self-healing and corrosion resistance recovery on magnesium alloys.